Metacognition in the own-race bias: Influences on restudy selection - DeLozier, Sarah, author; Rhodes, Matthew G., advisor; Clegg, Benjamin, committee member; Troup, Lucy, committee member; Martey, Rosa, committee member (Colorado State University. Libraries, 2015)
The own-race bias (ORB), refers to the finding that learners demonstrate poorer memory for faces of other races or ethnicities, compared to those of their own. This memory bias has been examined from an encoding perspective, yet little has been done to examine the possible contribution of metacognition. Under the assumption that monitoring affects control, recognition memory was examined for own-race (White) and other-race (Black) faces. Pilot data suggested that participants might be aware of the ORB, as evinced by their monitoring judgments. The experiment permitted participants to select faces for restudy, make delayed JOLs and restudy selections, then restudy selected faces prior to test. Results demonstrated similar monitoring accuracy for own-race and other-race faces, suggesting that the ORB may not be due to monitoring deficits. Measures of control provided some evidence that learners make similar control judgments for own- and other-race faces, and follow-up experiments are discussed.
Zip file contains appendix.
Keywords: metacognition; own-race bias; monitoring; control